Patient satisfaction with quality of care in public hospitals in Albania - Kalaja, Rezarta; Krasniqi, Marsida (Frontiers in Public Health, 2022)
Healthcare service quality and hospitalized patient satisfaction in Albania have never truly received the necessary attention. The aim of this study is the assessment of key elements of service quality and their relationship with patients' satisfaction with receiving healthcare at public health institutions in Albania. The study examines five key dimensions of quality such as responsiveness, reliability, assurance, tangibles, and staff empathy to assess properly the healthcare quality and patient satisfaction in Albania based on the SERVQUAL instrument, which measures the differences between patient's perceptions of service quality received, and their expectations in terms of these five dimensions. A total of 800 randomly selected patients were interviewed in the main cities of Albania in public hospitals. A respective literature review was also a necessity to determine not only the appropriate methodology to be applied, together with the right quality dimensions to use but also for a better understanding of the link between service quality and patient satisfaction. The determination of the main quality factors which contribute to patient satisfaction, as well as, their order of importance, is another key aspect of the study, which finalizes with appropriate recommendations that might help quality improvement in future. The analysis shows that overall patient satisfaction is affected in public hospitals by all dimensions of service quality. Therefore, patients' perspective is extremely important in assessing healthcare service quality and should be taken into consideration by healthcare managers and policymakers in Albania, whenever significant reforms will be undertaken to improve the quality of services in this sector.